Shortage of circulating naive CD8+ T cells provides new insights on immunodeficiency in aging - Fagnoni, Francesco F.; Vescovini, Rosanna; Passeri, Giovanni; Bologna, Giovanni; Pedrazzoni, Mario; Lavagetto, Giampaolo; Casti, Amos; Franceschi, Claudio; Passeri, Mario; Sansoni, Paolo (Blood, 2000)
Clinical observations indicate that elderly people are prone to severe, often lethal infectious diseases induced by novel pathogens. Since the ability to mount primary immune responses relies on the availability of naive T cells, the circulating naive T-cell reservoir was evaluated throughout the human life span. Naive T cells were identified as CD95− T lymphocytes for their phenotypic and functional features. Indeed, the lack of CD95 marker is sufficient to identify a population of naive T cells, as defined by coincidence with previously characterized CD45RA+ CD62L+ T cells. Naive CD95− T cells, as expected, require a costimulatory signal, such as CD28, to optimally proliferate after anti-CD3 stimulation. Cytofluorimetric analysis of circulating T lymphocytes from 120 healthy subjects ranging in age from 18 to 105 years revealed that naive T cells decreased sharply with age. The younger subjects had a naive T-lymphocyte count of 825 ± 48 cells/μL, and the centenarians had a naive T-lymphocyte count of 177 ± 28 cells/μL. Surprisingly, the naive T-cell count was lower in CD8+than in CD4+ subsets at any age, and the oldest individuals were almost completely depleted of circulating naive CD8+ T cells (13 ± 4 cells/μL). Concomitantly, a progressive expansion of CD28− T cells occurs with age, which can be interpreted as a compensatory mechanism. These data provide new insights into age-related T-cell–mediated immunodeficiency and reveal some analogies of T-cell dynamics between advanced aging and human immunodeficiency virus (HIV) infection. In conclusion, the exhaustion of the naive CD8+ T-cell reservoir, which has never been reported before, suggests that this T-cell pool is a major target of the aging process and may define a parameter possibly related to the life span of humans.